Fine-tuning of secondary arbor development: the effects of the ecdysone receptor on the adult neuronal lineages of the Drosophila thoracic CNS. - Brown, H.L.; Truman, J.W. (Development, 2009)
The adult central nervous system (CNS) of Drosophila is largely composed of relatively homogenous neuronal classes born during larval life. These adult-specific neuron lineages send out initial projections and then arrest development until metamorphosis, when intense sprouting occurs to establish the massive synaptic connections necessary for the behavior and function of the adult fly. In this study, we identified and characterized specific lineages in the adult CNS and described their secondary branch patterns. Because prior studies show that the outgrowth of incumbent remodeling neurons in the CNS is highly dependent on the ecdysone pathway, we investigated the role of ecdysone in the development of the adult-specific neuronal lineages using a dominant-negative construct of the ecdysone receptor (EcR-DN). When EcR-DN was expressed in clones of the adult-specific lineages, neuroblasts persisted longer, but we saw no alteration in the initial projections of the lineages. Defects were observed in secondary arbors of adult neurons, including clumping and cohesion of fine branches, misrouting, smaller arbors and some defasciculation. The defects varied across the multiple neuron lineages in both appearance and severity. These results indicate that the ecdysone receptor complex influences the fine-tuning of connectivity between neuronal circuits, in conjunction with other factors driving outgrowth and synaptic partnering.